Industry 4.0 readiness in west of Ireland small and medium and micro enterprises – an exploratory study. Issue 2 (3rd April 2023) - McDermott, Olivia; Nelson, Stuart; Antony, Jiju; Sony, Michael
Abstract: This study looks to understand the uptake of Industry 4.0 and digital technologies by Small and Medium Enterprises and Micro Enterprises in the West of Ireland with a focus on the challenges of Industry 4.0 as well as current integration levels of Industry 4.0. This study finds that there is a high level of awareness of Industry 4.0 and digitalization and its benefits within West of Ireland SME's and Micro enterprises. However, a sizeable majority are not implementing any Industry 4.0 projects currently, nor is it a part of their strategy. 53% of participant organizations had implemented Lean, with 97% of those only implementing within the last 2 years. The challenges to Industry 4.0 were high costs, lack of state support and fear of choosing the wrong equipment/solution. This is the first empirical study on Industry 4.0 readiness within the West of Ireland Small, Medium and Micro Enterprise space which investigates the understanding of and the readiness for Industry 4.0 as well as the motivation and support required by these enterprises for Industry 4.0. Organizations, including government bodies, can use this study to understand the readiness for digitalization and Industry 4.0 in smaller enterprises as opposed to larger enterprises.